Implementasi Pemantauan dan Evaluasi Penyelenggaraan Pelayanan Publik (PEKPPP) dalam Pengelolaaan Data dan Informasi Kinerja Unit Pelayanan Publik di Kecamatan Bubutan Kota Surabaya - Kharima, Evianti; Arundinasari, Indira (IAI Nasional Laa Roiba Bogor, 2024)
Public service is a series of activities in order to fulfill the service needs of every citizen and resident for goods, services, or administrative services provided by public service providers in accordance with statutory regulations. This is regulated by Law Number 25 of 2009 concerning Public Services. Monitoring and Evaluation of Public Service Provider Performance (PEKPPP), is an effort to carry out systematic measurements on a work unit within a certain period of time to obtain a public service index value. Monitoring and Evaluation of Public Service Provider Performance (PEKPPP) is carried out annually by the Ministry of Administrative Reform and Bureaucratic Reform (PANRB). The purpose of this research is to gain an understanding of how PEKPPP is implemented in Bubutan Sub-district. This research used descriptive qualitative research method. Data collection used in this research was based on observation techniques, structured interviews and documentation. Data analysis techniques included data reduction, data presentation, and conclusion drawing or data verification. The results show that the implementation of PEKPPP in Bubutan Sub-district is considered successful and well executed, leading to an increase in the IPP value to 4.72 in 2024. This is analyzed through Edward III's implementation theory which consists of four aspects, namely communication, resources, disposition and bureaucratic structure.